2017
DOI: 10.1371/journal.pone.0184876
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of an oxycodone vaccine: Addressing some of the unique considerations posed by opioid abuse

Abstract: Among vaccines aimed at treating substance use disorders, those targeting opioids present several unique medication development challenges. 1) Opioid overdose is a common complication of abuse, so it is desirable for an opioid vaccine to block the toxic as well as the addictive effects of opioids. 2) It is important that an opioid vaccine not interfere with the action of opioid antagonists used to reverse opioid overdose or treat addiction. 3) Some opioids are immunosuppressive and chronic ongoing opioid use c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 44 publications
1
63
0
Order By: Relevance
“…To measure drug-specific serum IgG antibody titers, morphine or oxycodone haptens conjugated to bovine serum albumin were coated on enzyme-linked immunosorbent assay plates at 5 ng/well in carbonate buffer (pH 9.6) and blocked with 1% gelatin (Pravetoni et al, 2012c;Raleigh et al, 2013Raleigh et al, , 2017. Goat anti-rat IgG conjugated to horseradish peroxidase was used as secondary antibodies (Jackson ImmunoResearch Laboratories, Inc., West Grove, PA).…”
Section: Antibody Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure drug-specific serum IgG antibody titers, morphine or oxycodone haptens conjugated to bovine serum albumin were coated on enzyme-linked immunosorbent assay plates at 5 ng/well in carbonate buffer (pH 9.6) and blocked with 1% gelatin (Pravetoni et al, 2012c;Raleigh et al, 2013Raleigh et al, , 2017. Goat anti-rat IgG conjugated to horseradish peroxidase was used as secondary antibodies (Jackson ImmunoResearch Laboratories, Inc., West Grove, PA).…”
Section: Antibody Characterizationmentioning
confidence: 99%
“…M-KLH effects on respiratory depression were not studied in the highdose heroin group because they had received naloxone to prevent respiratory arrest and OXY-KLH effects were not reported for the low-dose oxycodone group because controls did not show significant respiratory depression. However, OXY-KLH has been shown to reduce oxycodone-induced respiratory depression following a cumulative subcutaneous oxycodone dose of 9 mg/kg (Raleigh et al, 2017). Protection against opioid-induced respiratory depression is of note because respiratory depression is the principal mechanism of death from opioid overdose.…”
Section: Efficacy Of Vaccines For Opioid Use Disordersmentioning
confidence: 99%
“…The fentanyl vaccine was developed using a fentanylbased hapten (F) conjugated to either the native decamer keyhole limpet hemocyanin (KLH) carrier protein or the GMPgrade subunit KLH (sKLH) by means of a tetraglycine linker using carbodiimide chemistry to create F-KLH and F-sKLH, respectively. This vaccine design is analogous to other opioid vaccines that are being prepared for clinical use (Raleigh et al, 2017(Raleigh et al, , 2018. Mice and rats immunized with F-KLH had lower fentanyl-induced antinociception compared with controls.…”
Section: Introductionmentioning
confidence: 96%
“…Opioid vaccines have been explored preclinically as a treatment of OUD and have been effective in rodent and nonhuman primate models (Stowe et al, 2011;Bremer and Janda, 2012;Pravetoni et al, 2012b;Matyas et al, 2013;Raleigh et al, 2013Raleigh et al, , 2014Raleigh et al, , 2017Schlosburg et al, 2013;Bremer et al, 2014Bremer et al, , 2017. Opioid vaccines elicit opioid-specific antibodies that bind to the targeted opioids in the blood and reduce their distribution to the brain, reducing their behavioral and toxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that active immunization with the oxycodone vaccine OXY-KLH reduced oxycodone distribution to the brain in mice and rats, 2,3 and prevented oxycodone-induced behavior and toxicity associated with overdose. 31 However, this is a first report of using oxycodone-induced motor activity to select a lead vaccine formulation. To date, OXY-KLH has been formulated in alum, Freund's, MPLA, and alum mixed with MPLA.…”
Section: Discussionmentioning
confidence: 94%